Envolvimento participativo de famílias no processo de apoio em Intervenção Precoce na Infância Participatory involvement in Early Childhood Intervention - Marisa Alexandra Maia Machado; Paula Ângela Coelho Henriques dos Santos; Marilyn Espe-Sherwindt (Escola Superior de Educação de Paula Frassinetti, 2017)
Data de Submissão: 12-10-2017 Data de Aceitação: 22-12-2017 A influência que a família exerce sobre o desenvolvimento da criança conduz à importância da adoção de práticas que promovam o envolvimento participativo da família. Daí a dimensão participativa, caracterizadora de inclusão, se relevar como componente diferenciadora no processo de apoio em Intervenção Precoce na Infância. Assim, este estudo exploratório utilizou o triângulo das práticas de ajuda eficaz, com enfoque no vetor envolvimento participativo, como quadro teórico, para obter uma melhor compreensão acerca as oportunidades proporcionadas à participação das famílias apoiadas; e as suas expectativas quanto às práticas participativas. Encontrámos evidências congruentes com os princípios da abordagem centrada na família, emergindo passíveis implicações, essencialmente, sobre redes de suporte. The child's development process occurs in the context of her/his involvement in meaningful relationships with "reference persons" - those who, by responding in a contingent, regular and consistent manner to the child's basic needs, become "special", unique to her/him; in most cases, they're the child's family, and their involvement and participation in the Early Childhood Intervention (ECI) process is an essential component for its success, and a key in the path towards the child's educational and social inclusion. This exploratory study, based on the framework of the "ECI effective help-giving practices" advocated in the literature, aims to obtain a better understanding of (i) families' perception about the opportunities they are offered to participate in the process of supporting their children, and (ii) about their expectations regarding the professional practices providing this participation. The generated data indicate that the inquired families (represented by three mothers) experience a family centred approach that they recognize as a way for the social and educational inclusion of their children, and stress the importance of identifying support networks - formal and informal - in their lives and their children's. Keywords: Early Childhood Intervention; Help-giving practices; Family centred practices; Participatory involvement; Social and Educational Inclusion